Pengaruh Sikap Kreatif terhadap Prestasi Belajar Matematika - Farida, Nurul (AKSIOMA (Jurnal Pendidikan Matematika), 2014)
The aim of the research was to determine the effect of creative attitude on mathematics achievement. The population was the students in grade VIII junior high school in Central Lampung Regency. The conclusions of the research was students who have high creative attitude have better mathematics learning achievement than students who have middle and low creative attitude